The history of Chinese rhetoric - Wei, Weixiao, author.
1 online resource (148 pages)
Keywords: "This book challenges the existing misconception that there was no rhetoric in ancient China. Instead, this book provides ample evidence from public speeches in Xia dynasty and oracle bone inscriptions in Shang dynasty to public debates about government policies in Han dynasty to show that persuasive discourse and rudimentary rhetorical techniques already existed in ancient China. Using literary analysis and discourse analysis methods, this book explains how the Mandate of Heaven was inscribed at the core of Chinese rhetoric and has guided Chinese thoughts and expressions for centuries. This book also demonstrates Chinese rhetorical wisdom by extracting many concepts and terms related to language expression, persuasive speech, morality and virtue, life and philosophy and so on from great Chinese literary works. Well-known names such as Confucius, Laozi, Sima Qian, Liu Xie, Mozi, Hanfeizi, Guibuzi and so on, are all touched upon with their famous theory and sayings related to and explicated from the rhetorical perspective. Many surprising facts are found by the author and revealed in the book. For example, a thousand year ago, the Chinese author Liu Xie already found that all words have preferred lexical neighbours and structural environment. This is later on 'discovered' by corpus linguistics and illustrated, for example, by the concepts of collocation and pattern grammar. This book targets postgraduate students, teachers, researchers and scholars interested in advanced Chinese language and Chinese literature, history and culture"--